2019
DOI: 10.1371/journal.pone.0220934
|View full text |Cite
|
Sign up to set email alerts
|

Profiling DNA methylation patterns of zebrafish liver associated with parental high dietary arachidonic acid

Abstract: Diet has been shown to influence epigenetic key players, such as DNA methylation, which can regulate the gene expression potential in both parents and offspring. Diets enriched in omega-6 and deficient in omega-3 PUFAs (low dietary omega-3/omega-6 PUFA ratio), have been associated with the promotion of pathogenesis of diseases in humans and other mammals. In this study, we investigated the impact of increased dietary intake of arachidonic acid (ARA), a physiologically important omega-6 PUFA, on 2 generations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…It is plausible that this effect is partly due to nutritional programming. Previous studies in zebrafish (Danio rerio) have shown that parental nutritional programming through increased dietary intake of arachidonic acid or deficiency in 1-C nutrients results in DNA methylation changes and epigenetic regulation of gene expression in the liver of the offspring [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that this effect is partly due to nutritional programming. Previous studies in zebrafish (Danio rerio) have shown that parental nutritional programming through increased dietary intake of arachidonic acid or deficiency in 1-C nutrients results in DNA methylation changes and epigenetic regulation of gene expression in the liver of the offspring [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Parental high dietary ARA also modulates the DNA methylation patterns in the liver of zebrafish offspring. 165…”
Section: Referencesmentioning
confidence: 99%
“…In particular, lipid and retinoid metabolism by PPARα/RXRα, peroxisomal β‐oxidation and oestrogen signalling were affected. Parental high dietary ARA also modulates the DNA methylation patterns in the liver of zebrafish offspring 165 …”
Section: Functions Of Ara In Fishmentioning
confidence: 99%
“…The not-linear relationship of methylation with latitude in the eggs of T. dentatus can be explained by either the increased lipid metabolism or food supply at higher latitudes in our sampling area, both associated with decreasing temperatures and increasing productivity 36 . DNA methylation is a well-known process associated with lipid metabolism and synthesis pathway in humans 37 and, more recently, this association has been determined in fish 38 and invertebrates 39 . In a laboratory experiment, up to 333 differentially methylated regions between normal and caloric restricted fed individuals of the crustacean Daphnia magna were observed, suggesting that epigenetic processes could be involved in the expression of enzymes implicated in lipid synthesis pathways 40 .…”
Section: Discussionmentioning
confidence: 99%